Assessing User Experience (UX) Interacting with Car Catalog Application Using Multi-touch Tabletop Display - Abro, A. (Institute of Electrical and Electronics Engineers Inc., 2019)
Current car catalogue applications could well support multi-touch interactions but still suffer from poor usability and user experience (UX). These two aspects are important for design considerations as they could influence customers' decision making when purchasing the cars. This paper aims to present the design and evaluation of a 3D car catalogue application for car industry using tabletop display. The idea is to provide a platform to conduct an exploratory study in assessing how well UX could be supported by the application. The 3D car catalogue application is designed and developed based on existing design guidelines and collaborative activity theory. This design provides a proof of concept to leverage the use of table-top technology for car catalogue applications. In order to evaluate UX of the application, an empirical method is conducted using a set of UX questionnaires. The study findings provide reliability of the questionnaires. User feedback on UX reveals that the application supports co-located collaboration and usability but still lacks in providing better emotional aspect around tabletop display. Â© 2019 IEEE.